Identificação de SNPs (Single Nucleotide Polymorphisms) de suscetibilidade ao câncer em uma população miscigenada longeva do Nordeste Brasileiro - Galisa, Steffany Larissa Galdino (2020)
Cancer is the main cause of morbidity and mortality in the world, being considered a limiting factor for life expectancy. With aging, there is a higher incidence of cancer caused by physiological and genetic changes related to age. Single nucleotide polymorphisms (SNPs), the most common genetic changes in the human genome, can contribute to cancer susceptibility, acting as biomarkers. The objective of the work was to investigate the genetic mix of susceptibility to cancer in the long-lived population of Brejo dos Santos and carry out a study of ancestry. 73 healthy elderly people aged ≥80 years, living in the municipality of Brejo dos Santos - PB, were selected. The elderly were genotyped using the Axiom® Genome-Wide LAT 1 Array Plate SNP array platform. The Genotyping ConsoleTM software (Version 4.2; Affymetrix Inc.) was used for genotype analysis and quality control, applying the filters: SNP call rate> 97%; Hardy-Weinberg test (HWE) with p-value> 0.05, and the BRCA1, BRCA2, TP53, AURKA, CCND1, CDKN1A, ATM, ERCC5, XRCC1, MC1R, VEGF, MMP7, ERCC1, ERCC2, RB1, HNF1B genes , NCOA3, MLH1, MITF and CDH1. Ninety genetic variants of cancer susceptibility were identified, with 47.25% of the variants having European ancestry, 49.45% European / African ancestry and 3.29% of the European / Native American ancestry variants. Differences in allele frequency were observed between populations from different geographic regions such as Paraíba and São Paulo and in world populations. Of the 48 haplotypes identified in the population, 23 had only cancer risk alleles, five had risk increasing and decreased alleles, and five had only cancer protective alleles. The highest frequencies observed in the population were European haplotypes and European / African haplotypes with 45.83% each. Haplotypes of African origin had a frequency of 4.16%, and haplotypes European / Native American and European / African / Native American had a frequency of 2.08% each. In this work, we sought to combine the analysis of haplotypes in miscegenated groups to explore the genetic architecture of cancer in the population. The results provide the first report on common genetic polymorphisms of cancer in an inbred population of northeastern Brazil, which can establish a genetic-based database to guide future association studies.